High Frequency Jet Ventilation in Respiratory Failure Secondary to Respiratory Syncytial Virus Infection: A Case Series - Valentine, Kevin M.; Sarnaik, Ajit A.; Sandhu, Hitesh S.; Sarnaik, Ashok P. (Frontiers in Pediatrics, 2016)
Objective: To describe the utility of high frequency jet ventilation (HFJV) as a rescue therapy in patients with respiratory failure secondary to respiratory syncytial virus (RSV) that was refractory to conventional mechanical ventilation. Design: Descriptive study by retrospective chart review. Setting: Pediatric intensive care unit at a tertiary care children’s hospital. Patients: Infants on mechanical ventilation for respiratory failure due to RSV. Interventions: Use of high frequency jet ventilation. Main Results: Eleven patients were placed on HFJV. There was sustained improvement in ventilation on HFJV with a mean decrease in PCO2 of 9 mmHg at 24 hours and 11 mmHg at 72 hours. There were no significant changes in oxygenation by oxygenation index. No patients required extracorporeal support or suffered pneumothorax, pneumomediastinum or subcutaneous emphysema. Ten of 11 (91%) patients survived to discharge from the hospital. Conclusions: HFJV may represent an alternative therapy for RSV induced respiratory failure that is refractory to conventional mechanical ventilation.